Kesiapan Menghadapi Perubahan Pada Guru Sekolah Dasar Terhadap Pendidikan Multikultural - Kadek Ari Wisudayanti (Edukasi: Jurnal Pendidikan Dasar, 2021)
School is an institution that manages and administers education and teaching to students in an effort to achieve the expected goals and is a powerful place in building the intelligence, attitudes and skills of students in facing the realities of life. The concept of multiculturalism is sometimes a bit confusing, because it simultaneously refers to two different things, namely reality and ethics or practice and teaching. As a reality or practice, multiculturalism is understood as a productive representation of the interactions between various social elements in a collective level of life. As an ethic or teaching, multiculturalism refers to the spirit, ethos and beliefs of how the diversity of private and relatively autonomous social units, such as ethnicity and culture, should be managed in public spaces. Keyword: Teacher, School and Multiculture